Pemanfaatan Clay Tepung Sebagai Aksesoris Rambut - Restiana, Verna; Lutfiati, Dewi (Journal of Beauty and Cosmetology (JBC), 2020)
Flour-based clay are frequently used to create 3D figures, various handcrafts, along with a play and learning tool. Other than that, flour-based clay could also be an alternative material for accessory making. It is regularly made of corn starch, tapioca starch, rice flour, as well as white glue. To get the right dough consistency, finding out the accurate components and composition is needed. As a result, the finish product would be made into hair accessories. The technique used for making the hair accessory is wire wrapping. This research aims to find out the accurate dough components and composition, the ideal size of hair accessories, and wire-wrapped technique for accessory making. This research used literature review method, data are obtained from journals combined with articles that correlated with flour-based clay, hair accessories, including wire wrapping technique. Results from the data that has been obtained showed a good clay component consists of flour that contained amylose (tapioca flour, corn starch, et cetera), flour with higher amylopectin content for example waxy corn starch, waxy potato starch, and waxy rice starch, preservative, lubricant, white glue, and salt. The clay dough indicators are soft, pliant, non-sticky, low in viscosity, and resistant in retrogradation Based on the data, the ideal size of a hair accessory is 1:4 and one third from facial height. Jewelry making technique namely filigree and straw weaving could be applied for the purpose of making hair accessory.